0

# What is the formula of -2z-xyx 7 for x?

Updated: 12/14/2022

Wiki User

11y ago

-9

Elise Greenholt

Lvl 10
3y ago

Wiki User

11y ago

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc.

Terms like xyx and the absence of an operator between it and 7 suggest that some symbols are missing.

Earn +20 pts
Q: What is the formula of -2z-xyx 7 for x?
Submit
Still have questions?
Related questions

### How do you solve x to the 2nd power minus 49 equals 0?

There is a formula for "the difference of squares." (x + 7)(x - 7) = 0 x = 7, -7

### Which famous product is made with a secret ingredient called 'Formula 7-X'?

Which famous product is made with a secret ingredient called 'Formula 7-X' ?

### What is the formula for seven eights of sixteen?

7/8 x 16 = (7 x 16)/8 = 14

### Given the formula x2ab 7 find x if a3 and b5?

x=2(3)(5+7) x=6(5+7) x=30+42 x=72

6

### What is the answer for the formula x equals 2a b plus 7 find if a equals 3 and b equals 5?

x=2ab+7 x= 2(3)(5) +7 x=30+7 x=37

### What number is x when x squared plus 3x equals 7?

x2+3x = 7 x2+3x-7 = 0 Using the quadratic equation formula:- x = -4.541381265 or x = 1.541381265

### What is the formula for penicillin V?

(x-yr=7/8)+(yq/51)

### How do you factor x squared minus 47?

There's a formula for the "difference of squares." If your question was x2 - 49, the answer would be (x + 7)(x - 7). In your case, substitute the square root of 47 for the 7 in my example.

### What is the eighth term in the pattern with the formula 6n plus 7?

The formula is 6n + 7 where n is the nth term So 8th term would be (6 x 8) + 7 = 48 + 7 = 55

### What is the formula that converts x days to y weeks?

y= x/7 for example x=30 days y=? then y=30/7=4 week and 2 days

### Is there a formula that always give you 7?

If you set your equation to equal 7, then you can move 7 to the other side of the equation, and solve for x. This/these values will always result in 7. e.g. 3x2+11x+6=7 3x2+11x+6-7=7-7 3x2+11x-1=0 Factor using the quadratic formula and solve for x.